2013
DOI: 10.1016/j.nicl.2013.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Impaired and facilitated functional networks in temporal lobe epilepsy

Abstract: How epilepsy affects brain functional networks remains poorly understood. Here we investigated resting state functional connectivity of the temporal region in temporal lobe epilepsy. Thirty-two patients with unilateral temporal lobe epilepsy underwent resting state blood-oxygenation level dependent functional magnetic resonance imaging. We defined regions of interest a priori focusing on structures involved, either structurally or metabolically, in temporal lobe epilepsy. These structures were identified in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

21
96
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(117 citation statements)
references
References 73 publications
21
96
0
Order By: Relevance
“…We found that patients in the frequent-seizure group had increased connections within the temporal lobes bilaterally involving the seizure-prone medial temporal structure and bilateral primary auditory cortex, and those in the infrequent-seizure group had increased connections of the DMN. Observations of increased connectivity with other types of epilepsy, such as in the medial temporal lobes with mesial temporal sclerosis, 8,10 the lateral orbitofrontal lobes with absence seizures, 37 and frontal lobes with idiopathic generalized epilepsy, 38,39 make us surmise that increased connections are probably more specific to understand epileptogenesis. Previous studies also pointed to a temporal lobe origin in 67%-100% of patients with HWE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that patients in the frequent-seizure group had increased connections within the temporal lobes bilaterally involving the seizure-prone medial temporal structure and bilateral primary auditory cortex, and those in the infrequent-seizure group had increased connections of the DMN. Observations of increased connectivity with other types of epilepsy, such as in the medial temporal lobes with mesial temporal sclerosis, 8,10 the lateral orbitofrontal lobes with absence seizures, 37 and frontal lobes with idiopathic generalized epilepsy, 38,39 make us surmise that increased connections are probably more specific to understand epileptogenesis. Previous studies also pointed to a temporal lobe origin in 67%-100% of patients with HWE.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, hemispheric connectivity analysis in patients with unilateral mesial temporal sclerosis revealed decreased local and intrahemispheric connectivity and increased interhemispheric connectivity. 10 In contradistinction to the aforementioned results, there have been reports on increased hippocampal connectivity that was presumed to be a compensatory mechanism because it linearly correlated with a disease duration of Ͼ10 years. [1][2][3][4]6 Graph-theory analysis of resting-state fMRI data from patients with epilepsy also revealed decreased functional nodal topologic properties of the DMN that were positively correlated with disease duration.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…2 However, investigations involving large-scale network analysis have challenged this traditional conceptualization. 3,[5][6][7] Furthermore, several studies have reported an mTLE-related decrease in basal RS-FC in the epileptogenic hemisphere in brains of patients with mTLE, accompanied by contralateral compensatory mechanisms. 8,9 Many mTLE studies have focused on the epileptogenic zone, and most analyses that have investigated regions outside the hippocampus have focused on structural imaging technology.…”
mentioning
confidence: 99%
“…1,10,11 In contrast, few whole-brain functional network analyses of mTLE have been conducted. Structural MRI or electroencephalography or both incompletely measure temporal changes during the disease process, 5 while resting-state fMRI takes serial images during a time period that can capture the dynamic and evolving changes related to epilepsy. 12 The RS-FC derived from the fMRI images reflects functional aberrations and offers a network perspective on the psychiatric and cognitive complications of mTLE.…”
mentioning
confidence: 99%